Codesign is the zeitgeist of our time, but what do we mean by this? A scoping review of the concept of codesign in collaborative research with young people - Briony Lipton; Jodie Bailie; Helen Dickinson; Belinda Hewitt; Emma Cooper; Anne Kavanagh; Zoe Aitken; Marissa Shields (Health Research Policy and Systems)
Abstract Background Codesign is increasingly valued in health research as a way to actively include stakeholders in the research process, particularly for groups that have been historically excluded, such as young people. Despite its popularity, codesign is often inconsistently defined in literature. This creates challenges for applying it consistently across research projects and for evaluating its effectiveness. To address this definitional ambiguity, we conducted a scoping review to examine and clarify the concept of codesign in research with young people in the health and social sciences. Methods This scoping review drew on methodological guidance from JBI. Searches were conducted in Proquest, Scopus, Informit and Science Direct for relevant peer-reviewed publications for the period of January 2003–August 2023. Publications were included if they used the term codesign and/or related participatory research methods with young people aged 15–24 years. Screening, full-text review and data extraction were completed by two independent reviewers. Qualitative synthesis was used to identify definitions. Results The search yielded 1334 publications, with 49 meeting the inclusion criteria. Publications varied with respect to the age range of included young people and focused on a variety of populations, including young people with mental ill-health or with disabilities, First Nations youth and young people involved with specific services or programs. In analysing the way codesign was described, we found considerable variation, with most studies using multiple terms to refer to their methods. Common terms included coproduction (n = 21), coresearch (n = 15), participatory research (n = 10), codesign (n = 9) and participatory action research (n = 7). Conclusions Many different terms were used to describe codesign research with young people. Codesign was used and operationalized in a myriad of ways and overlapped with methods taken in other participatory approaches. This overlap may reflect the so-called blending of approaches in practice, highlighting the need to tailor different collaborative approaches to specific research projects, processes and participants. Ultimately, the ambiguity and overlap of terms describing collaborative methods such as codesign may matter less than the need for researchers to be transparent about their methods, their understanding of the terms and approaches they are using in research and their justification for undertaking collaborative research.